A study on the factors affecting the success of ERP SAP implementation in Malaysian Airlines Berhad : A case study mas finance division staffs / Wan Nor Syaheera Wan Mohd Sanusi - Wan Mohd Sanusi, Wan Nor Syaheera (Bachelor of Science (Hons.) Statistics, 2015)
This research examines the effect of system SAP reliability and Cash Management on the success of SAP implantation in Malaysian Airlines System Berhad. The research used to test several hypotheses by explaining the effect of variables or causal relationship among variable through hypothesis testing. This research is conducted at Malaysian Airlines Berhad in Subang which covered 111 staffs as respondents. The sample was drawn using collection of the returned questionnaires and then analysed using Structural Equation Modelling by using AMOS software. It is proven that the two independent variables have effect on the Staff Productivity Level in MAS thus, proven to part of factors affecting the success of the ERP SAP implementation